Reporting Under the International Covenant on Civil and Political Rights – Training Guide - United Nations for Human Rights Office of the High Commissioner (United Nations, 2021)
Part of the Professional Training Series (No. 23), this Guide aims to assist States parties by facilitating an understanding of the rights enshrined in the International Covenant on Civil and Political Rights and the corresponding obligations of the States. It is based on the provisions of the Covenant and the Committee’s general comments, jurisprudence on individual communications and concluding observations on State party reports, as well as reporting guidelines, rules of procedure, working methods and other documents. The Guide provides practical tools to enhance reporting skills with respect to the Covenant and the capacity to implement the Committee’s recommendations. It further serves as an analytical information and training tool for trainers to design and deliver courses on reporting to the Committee.